2003
DOI: 10.1038/sj.ejcn.1601711
|View full text |Cite
|
Sign up to set email alerts
|

Earlier smoking habits are associated with higher serum lipids and lower milk fat and polyunsaturated fatty acid content in the first 6 months of lactation

Abstract: Objective: To investigate the relation between maternal smoking habits, plasma lipids and milk fatty acid (FA) content and composition. Design: Breastfeeding mothers who gave birth to healthy, full-term infants were recruited. Mothers were interviewed on smoking habits, being defined smokers (S) when usually smoking at least five cigarettes per day before pregnancy. Setting: Department of Pediatrics, San Paolo Hospital, Milan, Italy. Subjects: In total, 92 mothers: 61 non-S (NS) and 31 S. Interventions: Pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 35 publications
2
22
1
7
Order By: Relevance
“…Our observations are consistent with lower total fat and DHA content of the milk from smoking mothers compared to non-smokers 8 and with a reduced synthesis rate of DHA from ALA in smokers 9 and breast cells exposed to products of cigarette smoke. 10 In 30-weeks gestational age preterms born to mothers reporting both smoking and alcohol use during pregnancy, DHA levels were higher at birth and rapidly decreased post-nataly, but the effects of alcohol and maternal smoking were not separated.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are consistent with lower total fat and DHA content of the milk from smoking mothers compared to non-smokers 8 and with a reduced synthesis rate of DHA from ALA in smokers 9 and breast cells exposed to products of cigarette smoke. 10 In 30-weeks gestational age preterms born to mothers reporting both smoking and alcohol use during pregnancy, DHA levels were higher at birth and rapidly decreased post-nataly, but the effects of alcohol and maternal smoking were not separated.…”
Section: Discussionsupporting
confidence: 93%
“…An associated increase in the 18 carbon precursor of the n-3 series, alpha-linolenic acid, ALA, was also noted 7. Our observations were consistent with earlier results showing that milk from smoking mothers had lower total fat and DHA content than milk from non-smokers8 and with the reduced rate of synthesis of long-chain polyunsaturated fatty acids (LCPUFA) in breast cells exposed to products of cigarette smoke compared with those that had not been exposed 9…”
supporting
confidence: 91%
“…Even considering the reduced LCPUFA content in the milk of smoking mothers,8 9 the limited milk volume intake of infants during the first 4 days of life would have a minimal effect on infants’ circulating LCPUFA. So, the differences observed in the neonatal LCPUFA pattern could mainly be ascribed to the direct effects of maternal smoking on LCPUFA metabolism and transport within separate compartments (maternal size, placenta and the fetus).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other reports claim decreased total cholesterol levels at 19 weeks of gestation in pregnant women who smoke. 44 Still others claim that smoking is associated with higher total cholesterol levels in pregnant women 45,46 ; however, both reports that claimed higher total cholesterol levels with smoking also showed that the average birthweight of children was higher in smoking mothers.…”
Section: Discussionmentioning
confidence: 96%